Wind plant system engineering through optimization of layout and yaw control. Issue 2 (18th March 2015) - Fleming, Paul A.; Ning, Andrew; Gebraad, Pieter M. O.; Dykes, Katherine
Abstract: Recent research has demonstrated exciting potential for wind plant control systems to improve the cost of energy of wind plants. Wind plant controls seek to improve global wind plant performance over control systems in which each turbine optimizes only its individual performance by accounting for the way wind turbines interact through their wakes. Although these technologies can be applied to existing wind plants, it is probable that the maximum benefit would be derived by designing wind plants with these capabilities in mind. In this paper, we use system engineering approaches to perform coupled wind plant controls and position layout optimizations of a model wind plant. Using several cost metrics, we compare the results of this optimization to the original plant and to plants in which the control or layout is optimized separately or sequentially. Results demonstrate that the benefit of this coupled optimization can be substantial, but it depends on the particular constraints of the optimization. Copyright © 2015 John Wiley & Sons, Ltd.